A pH-sensitive T7 peptide-decorated liposome system for HER2 inhibitor extracellular delivery: an application for the efficient suppression of HER2+ breast cancer. Issue 42 (29th September 2021) - Zhang, Shuangshuang; Sun, Qiaomei; Peng, Xu; Gan, Na; Zhao, Ludan; Suo, Zili; Zhao, Gang; Li, Hui
Abstract : An in vivo active-targeted transportation of T7-LP@LAP and acid-triggered drug release on the outer surface of HER2+ breast cancer cells. Abstract : HER2+ breast cancer is highly aggressive and proliferative even after multiple chemotherapy regimens. At present, the available clinical treatment duration of chemotherapeutic agents is limited by severe toxicity to noncancerous tissues, which are attributed to insufficient targeting. Here, we designed an active-targeted and pH-responsive liposome to improve the treatment. The ideas were as follows: (1) using liposome as a nano-delivery system for HER2 inhibitor (lapatinib; LAP) to reduce the toxicity; (2) modifying the capsule with T7 peptide for specific targeted delivery to the tumor cells, and (3) enabling the capsule with the pH-sensitive ability and triggering sustained drug release at extracellular weakly acidic microenvironment to emerge toxicity in tumors and to improve curative effects. It was found that T7 peptide-modified pH-sensitive liposome (T7-LP) was more effective and safer than free drug and unmodified liposome, and reduced drug-induced side effects and noncancerous toxicity. These results support the application potential of T7-LP in improving the efficacy of LAP in HER2+ breast cancer treatment. It might be a novel LAP formulation as a clinical agent.